2012
DOI: 10.1186/1471-2474-13-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postural balance in postmenopausal women and its relationship with bone mineral density- a cross sectional study

Abstract: BackgroundLow bone mineral density (BMD) and falls are common problems encountered in the postmenopausal women. The purpose was to evaluate the association between postural balance and BMD in postmenopausal women and its relation to risk for falls.MethodsIn this cross-sectional study, 225 women in amenorrhea > 12 months and age ≥ 45 years were included and divided, according to BMD, in T-score values > -2.0 SD (n = 140) and ≤ -2 SD (n = 85). Those with neurological or musculoskeletal disorders, history of vest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 29 publications
0
24
0
2
Order By: Relevance
“…Cangrussu et al (16) did not find significant differences between women with and without osteoporosis, for any variable of the force platform in bipodal support with eyes open. However, Burke et al (15) identified significantly higher postural oscillation in the eyes open task on the force platform on a stable surface in the group of women with osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cangrussu et al (16) did not find significant differences between women with and without osteoporosis, for any variable of the force platform in bipodal support with eyes open. However, Burke et al (15) identified significantly higher postural oscillation in the eyes open task on the force platform on a stable surface in the group of women with osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have found linear and consistent relations between muscular strength and BMD (7,8) , while the majority have found inconsistent results (9)(10)(11)(12)(13) . Similarly, when the variable refers to postural balance, a few studies have shown an inverse relationship between greater postural oscillation and BMD (14,15) , while the majority of studies have not identified any relationship (9,11,12,16) . However, to determine correlations between BMD and muscular strength or postural balance in postmenopausal women, some measurement conditions of these variables have not yet been tested, such as the isokinetic peak torque of knee extensors and flexors on an isokinetic dynamometer, or stabilographic analysis of postural oscillation on a force platform under challenging conditions, such as semi-tandem or unipodal support.…”
Section: Introductionmentioning
confidence: 99%
“…Ne postoji režim vežbanja koji je najbolji za sve osobe sa osteoporozom. Režim vežbi treba da bude individualno prilagođen na osnovu medicinske procene: rizika za prelom, mišićne snage, obima pokreta, nivoa fizičke aktivnosti, sposobnosti, hoda i balansa [16].…”
Section: Adaptirana Fizička Aktivnostunclassified
“…Postural stability and balance decrease with age [8]. Loss of balance and increased body sway are important risk factors for falls in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…The age-associated increase in the incidence of osteoporotic fractures results from a combination of increased fall risk and reduced bone strength. Although various factors are associated with falls, impaired balance and mobility have been consistently identified as the main risk factors [8]. Fall prevention should be routine in the management of postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%